Malay nationalism in the making of modern Malaysia: Abdul Majid Salleh and the Anti-British Movement in Johor 1946-1948 - Saat, Ishak; Mohd Yusoff, Kamaruzaman; Saidon, Mohd Kasri (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2017)
The political existence and shape of contemporary Malaysia cannot be divorced from the historic contributions made by Malay nationalism.Abdul Majid Salleh was one of the leaders of the Malay nationalism engaged in the political movement in the state of Johor.He was trying to persuade the Malays to rise and fight for their right.He was a young man who traveled from Perak to Johor to join and lead the anti-British movement in Johor.Anti British movement was in full swing at the time. Thus, Abdul Majid Salleh tried to enlighten the people of Johor to join in the nation-wide movement.This study described, by means of primary and secondary sources of information, Abdul Majid Salleh’s role and contribution in raising the Johor’s Malay political consciousness and in igniting the anti-British movement in Johor in the fight for the independence of Malaya.